1992
DOI: 10.1113/jphysiol.1992.sp019425
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hypertonic‐hyperoncotic solution and furosemide on canine hydrostatic pulmonary oedema resorption.

Abstract: SUMMARY1. This study aimed at enhancing the clearance of experimental hydrostatic pulmonary oedema in dogs using hypertonic-hyperoncotic solution (HHS) and furosemide.2. Anaesthetized dogs (n = 20) were mechanically ventilated with a positive endexpiratory pressure of 10 cmH20 (1-0 kPa).3. Hydrostatic pulmonary oedema was induced by inflating a balloon inserted into the left atrium and simultaneously infusing isotonic saline rapidly. Gedema formation was terminated by deflating the balloon and reducing the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…Our results are in agreement with previous studies that found an underestimation of EVLW by 30 -40% in similar OA models (23,24). Other studies in normal lungs or after indirect injury found either overestimation by the DI method or underestimation (6,11,(25)(26)(27)(28). This variability in correlation equations could depend on the type of animal model as well as on the type of methodology used.…”
Section: Evlw By DI Methods In Normal Lung or After Oa Injurysupporting
confidence: 93%
“…Our results are in agreement with previous studies that found an underestimation of EVLW by 30 -40% in similar OA models (23,24). Other studies in normal lungs or after indirect injury found either overestimation by the DI method or underestimation (6,11,(25)(26)(27)(28). This variability in correlation equations could depend on the type of animal model as well as on the type of methodology used.…”
Section: Evlw By DI Methods In Normal Lung or After Oa Injurysupporting
confidence: 93%
“…The circulatory response to HHS in this study is similar to those previously documented in hypovolaemic conditions (4,6,22) and during pulmonary oedema (10). We chose normovolaemic animals because in the hypovolaemic state basal lymph flows can be so small, making detection of decreased lymphatic flow impossible and subsequently, when oedema formation starts, the maximum lymph flow has already been attained.…”
Section: Discussionsupporting
confidence: 69%
“…This has led to the speculation that HHS might even be of therapeutic value in normo-and hypervolaemic conditions by mobilising extravascular fluid into the vascular compartment and increasing diuresis. In an earlier study, however, we found that rapid intravenous administration of HHS, in a canine hydrostatic pulmonary oedema model, did not influence the rate of reabsorption of oedema despite changes in parameters favouring oedema clearance (10). The aim of this study was to measure thoracic and abdominal lymph flows during the administration of HHS in an attempt to increase our understanding of HHS influence on pulmonary microcirculation and fluid balance in a lunghealthy nonhvpovolaemic condition.…”
mentioning
confidence: 94%
“…Appropriate mechanical ventilation strategies and diuretics are considered the mainstay of treatment for acute pulmonary oedema (Wickerts and others 1992). Furosemide, a loop diuretic, has been shown to assist resolution of pulmonary oedema and is thought to cause an increase in colloid oncotic pressure that facilitates resorption of extravascular fluid in the lungs (Wickerts and others 1991).…”
Section: Discussionmentioning
confidence: 99%